Migrant Workers and Social Protection in ASEAN: Moving towards a Regional Standard? - Hall, Andy (Journal of Population and Social Studies [JPSS], 2012)
The number of migrants originating from ASEAN member states is estimated at 13.5 million, 39 percent (5.3 million) of whom are working in other ASEAN countries. An estimated 60% of the working population in these countries work in informal sectors of the economy that are not fully covered by labor laws, let alone social protection measures. In addition, nascent social protection systems in these countries provide little coverage in case of loss of worker income, and standards are generally poorly enforced. In this context, migrant social protection in ASEAN has rarely been explored. This paper considers global standards and themes regarding migrant social protection before outlining case studies of Indonesia, Philippines, Singapore and Thailand. The paper shows how migrants rarely access social protection in ASEAN and recommends regional action by ASEAN member states to holistically remedy this.